A quality improvement project in autologous peripheral blood stem cell transplantation - Crosbie, C.; McConigley, Ruth (Transplant Nurses Association, 2011)
Stem cell transplantation (SCT) has been used for many years in the treatment of a variety of disorders. Although the basic rationale of transplantation as a treatment option remains the same, components of the transplant process have changed. There is an identified lack of literature on stem cell reinfusion procedures, particularly relating to training, quality and documentation. Furthermore, access to evidence-based guidelines that encourage education and reflection to improve care delivery is difficult for staff. A quality improvement project was conducted at Sir Charles Gairdner Hospital (SCGH) in Western Australia (WA) that involved education workshops and competency-based training and assessments. It aimed to provide nursing education and training relating to autologous SCT and to produce area-specific nursing practice guidelines. Education workshops were well attended and several staff members have completed their competencies as well as the self-directed learning package (SDLP) as a result of this project. This article aims to describe the project that enhanced staff training which led to improved patient care, communication and documentation.